Surface charge density determination in water based magnetic colloids : a comparative study - Campos, Alex Fabiano Cortez (2017)
This work focuses on the systematic investigation of the two well-established methods of structural surface charge density determination on magnetic colloids, labeled as Single Potentiometric Method (SPM) and Potentiometric-Conductometric Method (PCM). To compare some important features of the methods we determined the structural surface charge density of magnetic colloids samples based on CoFe2O4@ɣ-Fe2O3 core-shell nanoparticles with three different mean sizes using both strategies. Concerning quickness, easiness and cost, the PCM has proved to be more advantageous than the SPM. Regarding the effectiveness, both methods were consistent in determining the saturation value of the structural charge, but the SPM was more accurate to describe the pH-dependence of the concentration of the charged surface sites. Considering the chemical safety, the methods are equivalent. Finally, both the SPM and PCM are reproducible and can be effectively applied to determine the saturation value of the surface charge density on magnetic colloids.